A cultura no ensino de língua espanhola: crenças de três professoras e seus alunos - Torres, Maria Cristina Maldonado (2014)
The beliefs related to the process of teaching/learning of foreign languages are constructed based on the experiences of the participant professors and students. The beliefs show personal positions in front of foreign language and can suffer modifications over time when new experiences are acquired. This work aimed to understand the beliefs about culture in the teaching/learning process of ELE between professors and their students. The information necessary to the achievement of this research was obtained by using questionnaires. The theoretical background of this work was based in authors like Barcelos (1995, 2001, 2004, 2004a, 2004b, 2006, 2007) and Silva (2001, 2005, 2010) in the beliefs area. Thompson (2002), Kuper (2002), Geertz (1989), Sarmento (2004), Kramsch (2006) Miquel and Sans (2004) and Moran (2002) to define culture; being the last one who served as basis to categorize the definition about culture that was obtained from the beliefs of the participant professors and students. The analysis was based in a meta-cognitive analysis proposed by Barcelos (2001) that allowed to describe the contents through the participant's responses. The research had the participation of 35 students and 3 professors of the Literature course from the Federal University of Santa María. Some of the beliefs presented by the students were: the culture that is related with habits, traditions, folklore, daily activities from the people, relations between individuals, art, literature, music, culinary, beliefs of the people, values, among others. Most of the students consider that knowledge about cultural aspects can improve their performance in the studied language, and also believe that is possible to teach and learn any kind of cultural aspect independently of the level of expertise in the studied language, because for them language and culture cannot be separated. In the case of the participant professors it was obtained that two professors consider culture as a fundamental part of the language and they consider that when they teach a language are also teaching the culture. These professors also think that is possible to work in any aspect of the culture in the foreign language class. The third professor considers that language is something complex that is impossible to understand completely and as consequence its teaching is difficult in foreign language lessons. After the identification and comparison of the beliefs from the corpus data it was possible to conclude that student's beliefs in relation to the culture concept are influenced by two professors' beliefs. Additionally it was also observed that the students consider that culture is superficially explored in class. Finally, professors opine that the smaller amount of time in class has as consequence that cultural aspects are being superficially worked.